The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsestwater.1c00277
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Woodchip Bioreactor Characteristics and Their Influences on Joint Nitrate and Pesticide Removal

Abstract: We constructed a bench-scale continuous-flow (8 L total volume, 4.3 L/day) woodchip bioreactor and operated the reactor under field-like conditions to evaluate joint pesticide and nitrate removal. The continuous-flow reactor achieved 83.5 ± 8% diuron removal and 61.6 ± 11.9% imidacloprid removal with a 24 h hydraulic retention time (HRT). We designed a sequencing-batch reactor configuration (8 L total volume) to evaluate the impact of an aerobic phase on denitrification and pesticide removal performance. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 61 publications
3
6
2
Order By: Relevance
“…This lower NO 3 − reduction rate could be attributed to differences in condition and age of the reactors, considering anoxic conditions are preferred for denitrification (Payne, 1973;Seitzinger, 1988). However, in a bench-scale continuous flow woodchip bioreactor (8-L total volume), Wrightwood et al (2022) reported 55.6 ± 9.1% NO 3 − removal within a 12-h HRT, which is within the range observed in the current study.…”
Section: Bioditch Reactor Presencesupporting
confidence: 76%
“…This lower NO 3 − reduction rate could be attributed to differences in condition and age of the reactors, considering anoxic conditions are preferred for denitrification (Payne, 1973;Seitzinger, 1988). However, in a bench-scale continuous flow woodchip bioreactor (8-L total volume), Wrightwood et al (2022) reported 55.6 ± 9.1% NO 3 − removal within a 12-h HRT, which is within the range observed in the current study.…”
Section: Bioditch Reactor Presencesupporting
confidence: 76%
“…Sorption of imidacloprid to wood chips has been observed previously with 440–532 ng g −1 wood chips sorbed in one day and no significant sorption noted afterwards. 25 This value was lower than our observed average of 1185 ng g −1 d −1 sorption measured in the first seven days. Although the day 14 concentrations are anomalous, day 7 concentrations did not vary significantly from day 21 or day 28 values ( p = 0.31, 0.33).…”
Section: Resultscontrasting
confidence: 61%
“…Sorption of imidacloprid to wood chips has been observed previously with 440-532 ng g −1 wood chips sorbed in one day and no significant sorption noted afterwards. 25 This value was lower than our observed average of 1185 ng g −1 d −1 sorption measured in the first seven days.…”
Section: Imidacloprid Is Degraded By Non-cytochrome P450 Enzymes Unde...contrasting
confidence: 61%
See 2 more Smart Citations